A comparative analysis of testicular sperm morphology in fossorial and surface‐living skinks in South Africa. (2nd March 2018) - Verdú‐Ricoy, Joaquín; Matla, Tankiso; Gregory, Michael; Lambiris, Angelo; Jordaan, Adriaan; Zhao, Zhongning; Heideman, Neil
Abstract: We described for the first time the spermatozoan ultrastructure of the fully pentadactyl surface‐living skink Trachylepis punctatissima, and limbless fossorial skink Acontias meleagris . The spermatozoa of both species follow the general patterns observed within the Squamata. However, several important differences were detected between the two species in the head region (shape of the anterior acrosome, size of acrosome and nucleus) and especially in the midpiece (size of the midpiece, the presence of regular rows of dense bodies, size and number of mitochondria and beginning of the fibrous sheath). Both species shared more characters with the Sphenomorphus + Egernia group than with the Eugongylus group proposed by Jamieson, Oliver, and Scheltinga ( Acta Zoologica, 77, 85). Differences in the spermatozoan ultrastructure between T. punctatissima and A. meleagris could be due to distinct ecological and physiological requirements for fertilization, but additional research on these genera and within the Scincidae is required to disentangle this hypothesis, and to disentangle the phylogenetic relationships among skinks.